A CROSS-SECTIONAL STUDY ON THE ASSESSMENT OF KNOWLEDGE AND METHODS PRACTICED IN DISINFECTING AND DISPOSAL OF FACEMASKS AMONG THE GENERAL PUBLIC - SARJI, PAVITHRA S; POOJARY, NAGARATHNA; NEKKANTI, VINEELA; SRINIVASAN, R (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The vast amount of facemasks generated as waste should be disposed of appropriately and responsibly to prevent adverse effects on health and the environment. This study aims to assess the knowledge and methods commonly practiced by the public to disinfect and dispose of used facemasks. Methods: A cross-sectional study was conducted from June 2021 to December 2021 in the South Part of Karnataka using a face-validated questionnaire. The questionnaire included subject demographic details and methods to disinfect and dispose of masks. The data were recorded and analyzed using Microsoft Excel. Results: A total of (n=501) participants took part in the study. This study observed that the most commonly practiced method was to wash the masks with specific cleaners (n=259, 53%). We also assessed knowledge regarding the methods of disposal of a mask. The majority of the participants in our study are aware of the correct method for disposal of used masks(n=342, 68.26%), while (n=159, 31.73%) of subjects are not aware of the right facemask disposal method. Subjects who are educated (p=0.008) and regular mask users (p=0.011) are aware of the right method for mask disposal. Conclusion: Many people are unaware of the correct disposal methods. Hence, Manufacturers and Scientists should identify an effective way to disinfect and dispose of used masks and educate the public to practice the proper method of facemask disposal.